A cross sectional study between the prevalence of chronic pain and academic pressure in adolescents in China (Shanghai) - Zhang, Yongxing (BMC Musculoskelet Disord, 2015)
BACKGROUND: The purpose of this study was to investigate the prevalence of four types of chronic pain (headache, abdominal pain, neck and shoulder pain (NSP), and low back pain (LBP)) and to explore the relationship between the prevalence of chronic pain and self-reported academic pressure in high school students in Shanghai, China. METHOD: Three thousand students were randomly surveyed on related issues using a questionnaire, and the results were analyzed using a multivariate logistic regression model. RESULTS: Among the 2849 high school students who completed the questionnaire, the overall prevalence rates of headache, abdominal pain, NSP, and LBP were 30.3, 20.9, 32.8, and 41.1 %, respectively. The students in general experienced a heavy burden of learning, a high level of stress, and sleep deprivation, which were closely related to the four types of chronic pain. CONCLUSION: Chronic pain is a common condition in Chinese adolescents and is closely related to self-reported academic pressure.